1992
DOI: 10.3109/10799899209074792
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Anti-C-ERB A Antibodies Recognizing Native Thyroid Hormone Receptors: Their use to Detect the Expression and Localization of α and β C-ERB A Proteins in Rat Liver

Abstract: The cell-specific expression and tissue distribution of c-erbA proteins alpha and beta is still unknown. To address this problem, we prepared anti-peptide antibodies directed against epitopes of human (h) c-erbA, specific for the alpha or beta form of thyroid hormone receptors. The cDNAs coding for h c-erbA beta 1, alpha 1 and alpha 2 were transcribed and the mRNAs were translated in vitro in the presence of 35S-methionine, and then their reactivity with the antisera was evaluated. The antiserum anti-beta 62-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Several immunohistochemical studies have reported the presence of TR proteins in the liver of rodents and humans (Tagami et al 1990, Strait et al 1991, Macchia et al 1992, Rodd et al 1992, Falcone et al 1994. Although not all hepatocytes were stained in these studies, none of these studies mention a topographical distribution of TR isoforms even though most known T 3 -dependent genes are expressed in the liver in different zones.…”
Section: Discussionmentioning
confidence: 92%
“…Several immunohistochemical studies have reported the presence of TR proteins in the liver of rodents and humans (Tagami et al 1990, Strait et al 1991, Macchia et al 1992, Rodd et al 1992, Falcone et al 1994. Although not all hepatocytes were stained in these studies, none of these studies mention a topographical distribution of TR isoforms even though most known T 3 -dependent genes are expressed in the liver in different zones.…”
Section: Discussionmentioning
confidence: 92%
“…The characterization of these antipeptide polyclonal antibodies, competition studies (preadsorbing each antibody with the specific peptide or with the whole protein expressed in Escherichia coli) and immunoprecipitation analysis (immunoprecipitation of the protein translated in vitro and of the thyroid hormone receptor expressed in E. coli) were reported previously (26,27). Alpha-2-431 antibody activity could be blocked by an excess amount of immunizing peptide and by TR alpha-2 expressed in B. coli in both ELISA and western blotting analyses, but only a partial competition was obtained in our immuno¬ histochemical studies.…”
Section: Methodsmentioning
confidence: 99%
“…In this perspective, several attempts were conducted by different groups, the main strategy being based on the production of polyclonal antipeptide antibodies after selection of restricted sequences in regions that diverge between the known c-ErbA isoforms. In most studies, these antibodies were characterized mainly with recombinant c-ErbA iso¬ forms, and then used for immunohistochemical detec¬ tion (16)(17)(18)(19)(20)(21). Only a few reports provided data that indicate a discrimination between T3 receptor isoforms at the level of nuclear extracts (22,23).…”
mentioning
confidence: 98%